Segurança ambiental: mapa de riscos ambientais da pesca artesanal com espinhel, litoral nordeste do Pará - ARCANJO, Carlos de Souza (Universidade Federal do Pará, 2012)
This research was conducted in the Village of Caratateua and environs, part of the micro bragantina, northeastern Pará, in order to identify, assess and map the occupational risks inherent in the use of longline artisanal fisherman, through a qualitative assessment spot during the execution of this type of fishing, with the collaboration of participatory experienced fishermen. As a result, we elaborated a map of occupational risks of this type of fishing, which should be used in programs of occupational safety management (PPRA, PCMSO, PPP) preventers and public policy for the sector, being an important tool for the fisherman. Their analysis enables the identification, the layout of the desktop, accident vulnerabilities. This map helps you find practical solutions to eliminate or control risks in the process of longline fishing.